Edukasi Kesehatan Tentang Deteksi Dini dan Pencegahan Diabetes Melitus di Masyarakat - Naibaho, Eka Nugraha V.; Ritonga, Edisyah Putra; Silaban, Nataria Yanti; Hutagaol, Aureliya; Damanik, Hamonangan; Ritonga, Yuni Shanti; Nainggolan, Syahrul Handoko; Marbun, Trisnawati (CV. Devi Tara Innovations, 2026)
Diabetes mellitus is a chronic condition characterized by elevated blood glucose levels resulting from the body’s inability to produce sufficient insulin or to utilize insulin effectively. This community service activity was conducted using a direct observation method and was adapted to the environmental conditions of the Tanjung Mulia Hilir community, Medan, particularly in the Tanjung Mulia District. Preparation Stage: The activity was designed in the form of health education for the community, utilizing leaflet media and demonstrations of random blood glucose and blood pressure measurements. Implementation Stage: The activities included health education covering the definition of diabetes mellitus, signs and symptoms, risk factors, management strategies, and a question-and-answer or consultation session related to diabetes mellitus. Participants were also provided with explanations on how to perform self-monitoring of blood glucose, efforts to prevent hyperglycemia and hypoglycemia, followed by demonstrations of blood pressure and random blood glucose measurements using digital sphygmomanometers and glucometers. Evaluation Stage: Participants were informed of their examination results and categorized into low-risk or high-risk groups, followed by additional education tailored to their respective conditions. ased on the outcomes of this community service activity, it can be concluded that providing health education or counseling to the community significantly improves knowledge levels. Overall, this community service program contributed to increased public knowledge and enhanced community health status in the working area of the Tanjung Mulia Health Center, Medan.